Mobile ECMO for inter-hospital transport of pediatric patients: experience from 22 cases - Yang, Yufan; Wang, Xiangni; Lu, Xiulan; Zhang, Xinping; Huang, Jiaotian; Xiao, Zhenghui (Frontiers in Pediatrics, 2025)
ObjectiveTo summarize the management experience of inter-hospital transport of critically ill children with extracorporeal membrane oxygenation (ECMO) in our hospital and provide evidence for the mobile ECMO for inter-hospital transport of pediatric patients.MethodsCritically ill patients treated with ECMO transported to our hospital from January 2020 to July 2025 were included in this study and analyzed general information, disease types, cannulation methods, ECMO transport distances, patient conditions before and after ECMO deployment, complications during the transport, and outcome. The lesson was drawn up regarding individual protection, transport procedures, transport equipment, teamwork, monitoring during transport, and quality control, providing an evidence-based foundation for the mobile ECMO for inter-hospital transport process of critically ill children.ResultsA total of 22 critically ill pediatric patients were successfully transported to our hospital supported with ECMO by ambulance. The oldest child was 13-years-old, and the median age of the cohort was 76.00 (19.00, 132.00) months. The primary diseases included acute respiratory distress syndrome (ARDS), fulminant myocarditis, avian influenza, heart failure, and persistent pulmonary hypertension of the neonate. The median transport distance was 180.00 (134.00, 233.00) km, and the patients had no complications during the transport. Subsequently, 17 patients recovered and were discharged from the hospital. Five patients developed with multiple organ failure soon after the separation of ECMO. The ECMO duration was 126.50 (83.00, 155.00) h. No infection in any medical staff and nursing staff.ConclusionThe availability and safety of mobile ECMO for inter-hospital transport of critically ill children could be improved with the support of a well-equipped technical team in a time-effective manner, saving patient lives.